APOE Genotype Modifies the Plasma Oxylipin Response to Omega-3 Polyunsaturated Fatty Acid Supplementation in Healthy Individuals - Saleh, Rasha N. M.; West, Annette L.; Ostermann, Annika I.; Schebb, Nils Helge; Calder, Philip C.; Minihane, Anne Marie (Frontiers in Nutrition, 2021)
The omega-3 polyunsaturated fatty acids (n-3 PUFAs), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), mediate inflammation by affecting pro-inflammatory and anti-inflammatory/pro-resolving oxylipin concentrations. Common gene variants are thought to underlie the large inter-individual variation in oxylipin levels in response to n-3 PUFA supplementation, which in turn can contribute to the overall heterogeneity in response to n-3 PUFA intervention. Given its known role in inflammation and as a modulator of the physiological response to EPA and DHA, here we explore, for the first time, the differential response of plasma hydroxy-, epoxy- and dihydroxy-arachidonic acid, EPA and DHA oxylipins according to apolipoprotein E (APOE) genotype using samples from a dose-response parallel design RCT. Healthy participants were given doses of EPA+DHA equivalent to intakes of 1, 2 and 4 portions of oily fish per week for twelve months. There was no difference in the plasma levels of EPA, DHA or ARA between the wildtype APOE3/E3 and APOE4 carrier groups after 3 months or 12 months of n-3 PUFA supplementation . At 12 months, hydroxy EPAs (HEPEs) and hydroxy-DHAs (HDHAs) were higher in APOE4 carriers compared to wild type APOE3/E3 genotype, with the difference most evident at the highest EPA+DHA intake. A significant APOE*n-3 PUFA dose effect was observed for the CYP- hydroxylase products 19-HEPE (p=0.027) and 20-HEPE (p=0.011). 8-HEPE, which, along with several other plasma oxylipins, is an activator of peroxisome proliferator-activated receptors (PPARs), was the most increased oxylipins showed the highest fold change in APOE4 carriers (14-fold) compared to APOE3/E3 (4-fold) (p=0.014). Low basal plasma EPA levels (EPA< 0.85% of total fatty acids) were associated with a greater greater change in 5-HEPE, 9-HEPE, 11-HEPE and 20-HEPE compared to high basal EPA levels (EPA> 1.22% of total fatty acids).The higher levels of hydroxy-EPA and -DHA in APOE4 carriers post-intervention could be due to an increase in LDL or due to a compensatory response to increased inflammatory and oxidative stress in this genotype group. In conclusion, APOE genotype modulated the plasma oxylipin response to increased EPA+DHA intake, with APOE4 carriers presenting with the greatest increases following high dose n-3 PUFA supplementation for twelve months.